'Dear Colleague' letter urges behavioral telehealth expansion. Issue 22 (29th May 2020) - Canady, Valerie A.
Abstract : Citing concerns about mental health and addiction during these "tumultuous times, " members of Congress last month wrote a letter to congressional leaders urging for the expansion of behavioral telehealth services in any upcoming COVID‐19 response package.